Development of a novel fusion protein with Anaplasma marginale and A. centrale MSP5 improved performance of Anaplasma antibody detection by cELISA in infected and vaccinated cattle - Primo, María Evangelina; Thompson, Carolina Soledad; Valentini, Beatriz Susana; Sarli, Macarena; Novoa, María Belen; Mangold, Atilio Jose; Torioni, Susana Marta (Plos One, 2019)
Detection of antibodies to Anaplasma spp. using commercial competitive enzyme-linked immunosorbent assay (ccELISA) is based on the recombinant major surface protein 5 fused to maltose binding protein (MBP-MSP5) or glutathione S-transferase (GST-MSP5). To avoid false positive reactions due to the presence of antibodies against E. coli MBP in cattle, previous sera absorption is required. This study evaluated the replacement of MBP-MSP5 or GST-MSP5 antigens by the truncate MSP5 (residues 28–210) of A. marginale (tMSP5m), A. centrale (tMSP5c) and fusion protein MSP5 (tMSP5cm), expressed without N-terminus transmembrane helix in the ccELISA test. Immunoreactivity was evaluated by western blot using monoclonal antibodies against the tMSP5 and by in-house cELISA (hcELISA) with purified tMSP5m, tMSP5c or tMSP5cm using sera from cattle infected with A. marginale (n = 226) or vaccinated with A. centrale (n = 173) and uninfected cattle (n = 216). Results of hcELISA were compared with those of ccELISA. Recombinant protein was expressed highly soluble (> 95%) in E. coli without a molecular chaperone. Specificity of the hcELISA-tMSP5m, -MSP5c or -tMSP5cm was identical to (99.5%) and greater than that in ccELISA (96.3%). Sensitivity of hcELISA-tMSP5m and ccELISA was identical (95.5%), but lower than that of hcELISA-tMSP5cm (96.2%) and -tMSP5c (97.2%). The analysis of vaccinated cattle by hcELISA-tMSP5c showed sensitivity of 99.4%. In summary, the generation of fusion MSP5 A. marginale-A. centrale protein without transmembrane helix was a very effective method to express the recombinant protein highly soluble in the bacterial cytoplasm and contributed to an increased test performance for detecting antibodies in cattle naturally infected with A. marginale or vaccinated with A. centrale.